Estimating the exergy efficiency of engine using nanolubricants - Mohammadnejad, M.; Ghazvini, M.; Javadi, F.S.; Saidur, Rahman (Energy Education Science and Technology Part A: Energy Science and Research, 2011)
Friction is an effective factor in the reduction of the exergy efficiency in engines. In this study, the effects of using nanolubricants on friction reduction, thereby increasing the engine exergy efficiency, have been investigated. First, studies done on exergy, engine lubrication and friction reduction with nanolubricants have been reviewed. Based on these studies the mathematical formula for estimating the exergy efficiency of an engine that uses nanolubrication was derived. Finally, it has been found that adding CuO nanoparticles to SF oil has the greatest effect on the exergy efficiency improvement and the maximum amount of this improvement is 4.6.